Microstructural Studies on the October 2023 Edition Ketikpos.Com News Discourse - Puspita, Yenny; Rukiyah, Siti; Wardarita, Queen; Nasir, M; Sulasmi, Sulasmi; Nani, Rina Ayu Putri (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
This research aims to describe in depth several aspects of grammatical and lexical devices contained in the October 2023 edition of the Ketikpos.com news discourse, to indicate the dominant aspects of grammatical devices and lexical device aspects, and to indicate the types of devices whose appearance has excellent intensity in Ketikpos news discourse—.com October 2023 edition. Data analysis in this research used the magic method. This method describes several aspects of grammatical and lexical devices in the Ketikpos.com news discourse, October 2023 edition. Furthermore, this method can also identify the dominant aspects of grammatical and lexical devices and the types of devices used. Its appearance is intense in the Ketikpos.com news discourse, October 2023 edition. The approach used in this research is microstructural. The microstructural approach is an approach that examines discourse based on aspects of form and aspects of meaning. The form aspect is the birth structure of language, which includes grammatical aspects. The meaning aspect is the inner structure of language, which includes the lexical aspect.